Solar radiation measurements on Gara glacier (MAUSAM, 1978)
Solar radiation data collected during the 1910 interdisciplinary scientific expedition to Gara glacier are presented. The observations made include direct solar radiation, global solar radiation, reflected solar radiation from the underlying surface under different conditions and net radiation and extended over a period or 16 days at an altitude or 4700 m.The low value or direct solar radiation, viz.., 1.5.1.57 cal/cm2 suggests the atmosphere over the glacier is turbid mainly due to the relatively high water vapour content and particulate matter. The global solar radiation in September is or the order or 600 cal/cm2. The mean daily albedo was 0.77 when the underlying surface was covered with snow. The maximum net radiation over the glacier on 12 September 1975, a clear day was 0.98 cal/cm2 min around noon. The results are compared with ,similar observations made at the high altitude stations.